2009
DOI: 10.1186/1742-4690-6-86
|View full text |Cite
|
Sign up to set email alerts
|

Unintended spread of a biosafety level 2 recombinant retrovirus

Abstract: BackgroundContamination of vertebrate cell lines with animal retroviruses has been documented repeatedly before. Although such viral contaminants can be easily identified with high sensitivity by PCR, it is impossible to screen for all potential contaminants. Therefore, we explored two novel methods to identify viral contaminations in cell lines without prior knowledge of the kind of contaminant.ResultsThe first hint for the presence of contaminating retroviruses in one of our cell lines was obtained by electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…With regard to laboratory events, common cell lines have been shown to harbor XMRV and other retroviruses. 31,73 Human candidates for xenotransplantation of porcine tissue and organs might benefit from testing for XMRV infection to avoid possible recombination with porcine endogenous retroviruses. 74 Conclusions XMRV is the first human retrovirus to be discovered in many years and has generated considerable interest among both researchers and patients.…”
Section: Diagnosticsmentioning
confidence: 99%
“…With regard to laboratory events, common cell lines have been shown to harbor XMRV and other retroviruses. 31,73 Human candidates for xenotransplantation of porcine tissue and organs might benefit from testing for XMRV infection to avoid possible recombination with porcine endogenous retroviruses. 74 Conclusions XMRV is the first human retrovirus to be discovered in many years and has generated considerable interest among both researchers and patients.…”
Section: Diagnosticsmentioning
confidence: 99%
“…While we did not report on the viral findings, others have done so 14,15 and we refer to this XMLV strain as N417 although it has also been referred to as VB3.2. 21 Recent reports of squirrel monkey retroviruses (SMRV) infecting human cultures (by unknown routes or sources) and their possible large scale horizontal spread have also been published, 35,36 and several human cell lines for human immunodeficiency virus research were found to release infectious XMLV. 22,37 However, there are virtually no reports of contamination of xenograft cultures published during the past 15 y and most scientists appear unaware of the contamination problem (authors' observations).…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Gene sequences of the 1977 isolate and others collected in the 1950s were almost identical, indicating that the virus had not replicated and evolved in the interim, and had probably been held in a laboratory freezer between 1950 and 1977 and 'escaped' during passaging. The suggestion that persistently infected cells might be involved is also not outlandish; influenza virus can persistently and latently infect MDCK cells [27], and viruses do travel between laboratories in cells [28]. …”
Section: Circumstantial Evidencementioning
confidence: 99%